Short Thoughts at Length on The Actor’s Paradox - HATHÁZI, András (Studia Universitatis Babeș-Bolyai Dramatica, 2024)
Why the actor’s paradox? I would not even bother with this question if I didn’t see so many acting students desperate to do well what they are given as “course material” and so much outdated, dusty, outmoded, mannered acting on stages in their home countries. And even the latter would not interest me – since they are largely kept alive by public taste and public satisfaction (of very dubious value for me) – if they were not based on the same criteria on which I base my ideas about acting. So, under the pretext of the apparent contradiction in Diderot’s words, I will examine where I might have started in a different direction. At which fork in the motorway did I drive wrongly onto the motorway and go against the traffic? Because it is obvious to me: I am in the minority. Perhaps the paradox is not in the acting, but in the way we think about it.